Analisis Pengarusutamaan Gender di Kabupaten Polewali Mandar - Muthmainnah Putri Husaeni (Departemen Ilmu Pemerintahan Fisip Unhas, 2023)
Gender equality and women's empowerment are essential components of sustainable regional development. Gender Mainstreaming (GM) serves as a strategic approach to integrating gender perspectives into all development processes in order to reduce disparities between men and women in terms of access, participation, control, and benefits of development. This study aims to analyze the implementation of gender mainstreaming in regional development in Polewali Mandar Regency. The research employed a qualitative descriptive approach. Data were collected through interviews, observations, documentation, and literature review involving the Regional Research, Development, and Planning Agency (Balitbangren), the Office of Population Control, Family Planning, Women's Empowerment and Child Protection (DP2KBP3A), and the Social Affairs Office of Polewali Mandar Regency. Data analysis was conducted through data reduction, data presentation, and conclusion drawing. The findings indicate that gender mainstreaming in Polewali Mandar Regency has been implemented through three main aspects: planning, implementation, and organization. In the planning aspect, gender perspectives have been integrated into regional development planning documents and gender-responsive programs and budgets. In the implementation aspect, various activities such as training programs, socialization, preparation of regional gender profiles, and capacity-building initiatives for government agencies have been conducted to support gender mainstreaming policies. Meanwhile, in the organizational aspect, the local government has established a Gender Mainstreaming Working Group (Pokja PUG) to strengthen coordination and collaboration among regional government agencies.